1995
DOI: 10.1080/00102209508951894
|View full text |Cite
|
Sign up to set email alerts
|

BI-Modal Size Distributions Predicted by Maximum Entropy are Compared with Experiments in Sprays

Abstract: A theoretical formulation based on maximum entropy principles is presented to predict the droplet size and velocity distributions of sprays in an isothermal environment. The joint droplet distribution function is derived subject to the constraints of mass flow rate, momentum flux, and two modes of energy fluxes(kinetic and surface). A simpler model, which reduces the number of constraints by three, is derived by choosing an adequate velocity integration range. This maximum entropy principle spray model is test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Van der Geld and Vermeer [229] used the normalization condition along with the conservation of mass and surface energy as constraints in the maximum entropy model and were able to predict a bimodal distribution of droplet size in a spray due to the occurrence of the satellite droplets. Such bi-modal droplet distribution was also predicted by Chin et al [230], who accounted momentum conservation in the three co-ordinate directions. The source terms were carefully evaluated using the necessary experimental data.…”
Section: Mep Applications In Spray Characterization: State Of the Artsupporting
confidence: 56%
See 1 more Smart Citation
“…Van der Geld and Vermeer [229] used the normalization condition along with the conservation of mass and surface energy as constraints in the maximum entropy model and were able to predict a bimodal distribution of droplet size in a spray due to the occurrence of the satellite droplets. Such bi-modal droplet distribution was also predicted by Chin et al [230], who accounted momentum conservation in the three co-ordinate directions. The source terms were carefully evaluated using the necessary experimental data.…”
Section: Mep Applications In Spray Characterization: State Of the Artsupporting
confidence: 56%
“…The predicted results showed a good fit with the experiments. Chin et al [230] concluded that an increase in the number of velocity components in the prediction improve the predictive capability of the model and pointed out the role of azimuthal momentum source term in increasing the bimodality of the distribution. However, later on Chin et al [231] proposed another MEP based model using only one component of velocity along with two additional constraint equations.…”
Section: Mep Applications In Spray Characterization: State Of the Artmentioning
confidence: 99%
“…Bi-modal drop-diameter distributions were also obtained by Chin et al [27] who generalized Chin et al [24] formulation by accounting for the three components of drop velocity, i.e., d = dVdU x dU y dU z . Following Sellens' approach [21] [22] reported an acceptable fit on the number-based drop-diameter distribution of a spray produced by a swirl atomizer.…”
Section: Application Of Mef To Determine Liquid Spray Drop-size Distrmentioning
confidence: 99%
“…This new formulation allowed bi-modal distributions to be obtained. Considering this approach and the one due to Chin et al [27], it seems that a minimum of seven parameters is required if one has to represent bi-modal drop-size distribution. Chin et al [28] performed an experiment where droplets produced by a liquid column were visualized by a high-speed camera (1,500 images/s).…”
Section: Application Of Mef To Determine Liquid Spray Drop-size Distrmentioning
confidence: 99%
See 1 more Smart Citation